2022
DOI: 10.30892/gtg.43301-895
|View full text |Cite
|
Sign up to set email alerts
|

Current Problems in the Tourism and Hotel Industry Taking the World's Tourist Cities as an Example

Abstract: Chinese tourism companies are facing problems such as over-exploitation of tourism resources, severe homogeneity of tourism service products, and gradual decline in corporate competitiveness. The article aims to provide the theoretical basis and experience for Chinese tourism to go abroad and develop international operations. This article uses a combination of qualitative and quantitative analysis methods. This article analyzes Singapore's tourism investment environment in many aspects, based on the existing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The data sets include representatives from aviation, resorts and hotels, tour operators, and travel agents from India. This investigation triggers extreme vulnerability witnessed among the tourism and hospitality business from an Indian perspective (Kulakhmetova et al, 2022). The study revealed the major socio-psychological challenges at multiple levels navigating newer dimensions to handle the tourism business.…”
Section: Study Settingsmentioning
confidence: 96%
“…The data sets include representatives from aviation, resorts and hotels, tour operators, and travel agents from India. This investigation triggers extreme vulnerability witnessed among the tourism and hospitality business from an Indian perspective (Kulakhmetova et al, 2022). The study revealed the major socio-psychological challenges at multiple levels navigating newer dimensions to handle the tourism business.…”
Section: Study Settingsmentioning
confidence: 96%